Minimizing The Risk of Foreign Exchange Transactions in Facing Foreign Exchange Exposure - Achda Vellanita; Zulfikar Steifani Prayoga; Agus Sukoco; Gede Arimbawa; M. Ikhsan Setiawan (Journal of International Conference Proceedings (JICP), 2018)
The purpose This study discusses how to minimize foreign exchange transaction risk by using hedging technique method. Where this research performs actions taken to protect a company against exchange rate exposure and to measure the extent to which a company can be influenced by the exchange rate. Method, This research is quantitative descriptive by analyzing forward contract method in facing foreign exchange exposure. Calculates the forward rate used to hedge the net assets and liabilities of the company in foreign currency. Result,By using the contractual forward contract hedging method, the forward contract hedging method is more profitable than using open position method to face foreign exchange exposure. From the data obtained forward contract hedging method provides exchange rate advantage of Rp 36.877.227.752.936 while the open position method provides for foreign exchange loss of Rp 36.877.227.752.936 The findingsFrom this study companies that conduct international transactions or exposure and imports are influenced by fluctuations in foreign exchange rates. The MNC company will be able to reduce the risk of currency fluctuation losses, so as not to have a worse impact on the company Keywords: foreign exchange, hedging, risk ,currency